Functional Involvement of Interferon-Inducible Transmembrane Proteins in Antiviral Immunity - Liao, Yuan; Goraya, Mohsan Ullah; Yuan, Xu; Zhang, Baoge; Chiu, Shih-Hsin; Chen, Ji-Long (Frontiers in Microbiology, 2019)
Abstract: Interferons (IFNs) play crucial roles in host defense against viral infections by inducing the expression of numerous IFN-stimulated genes (ISGs) that can activate host antiviral immunity. Interferon-inducible transmembrane proteins (IFITMs), a family of small transmembrane proteins, are critical ISG products. Compelling evidence has implicated that IFITMs can establish an innate immune state to eliminate pathogens efficiently. IFITM proteins can impede broad-spectrum viral infection through various mechanisms. It is generally believed that IFITMs can block the viral entry by suppressing viral membrane fusion. However, some findings indicated that IFITMs might also inhibit viral gene expression and viral protein synthesis and thereby impair viral replication. IFITMs may incorporate into virions during viral assembly and thus reduce the infectivity of nascent virions. The precise inhibitory mechanism of IFITMs on viral infection and replication still requires further exploration. In this review, we highlight the recent findings regarding critical roles of IFITMs in host-virus interaction. We also discuss the molecular mechanisms underlying their functions in antiviral responses.